Vintage type and graphics : an eclectic collection of typography, ornament, letterheads, and trademarks from 1896-1936 - Heller, Steven, 1950-; Fili, Louise, ....- (New York : Allworth Press, 2011)
Exquisite graphic design artifacts comprise this unusual collection culled from the pages of type and typography books dating from 1896 to 1936. Design professionals, students and teachers of graphic design, and anyone with an interest in vintage design will be delighted to ?nd rare, never-before-reprinted type specimens, vintage layouts, logos, and decorations that will serve as an inspiration and resource for practicing and aspiring graphic designers.
"Includes all images disk"--Cover.
Includes bibliographical references.
Keywords: Type and type-founding -- Specimens; Type and type-founding -- History -- 19th century -- Pictorial works; Type and type-founding -- History -- 20th century -- Pictorial works; Type ornaments -- Specimens